Synthesis of silica coated plasmonic metal nanostructures - Oi, Sok Yee (Nanyang Technological University, 2020)
Plasmonic metal nanoparticles, particularly Silver and Gold, have been extensively studied due to their unique optical properties which are governed by the Localized Surface Plasmon Resonance (LSPR). The optical properties can be tuned by precise control of size, shape and composition of nanoparticle. Compared to monometallic structures, the size effect due to a bimetallic component have greater significance. Among the different orientations, the core/shell nanostructures of Ag @ Au have high potential for their catalytic activities, at the same time, providing chemical stability. A dielectric material such as silica coating is often employed as a physical barrier to prevent nanoparticles from aggregation, which also give rise to a higher photocatalytic activity. In this project, bimetallic nanostructures with tunable shell thickness of silica (Ag @ Au @ SiO¬2) were synthesized. The resulting nanostructures were characterized by UV-Vis spectroscopy, Transmission Electron Microscopy (TEM) and Energy-dispersive X-ray Spectroscopy (EDX). In the process, parameters like the amount of gold growth solution used and the amount of precursor for silica coating are tuned. From the project, the nanoparticles formed with a 4mL of gold growth solution gave a uniform coating of Au while maintaining its spherical shape. On the other hand, tunable silica shell thickness was successfully synthesized by varying the amount of Ag @ Au used. With a greater amount of Ag @ Au used (5mL), the final nanostructures of Ag @ Au @ SiO2 have a resulting silica shell thickness approximately 1.8nm. Likewise, the silica shell thickness is approximately 11nm when 1mL of Ag @ Au was used. As the project does not include the testing of photocatalytic applications, the effect of silica shell thickness on actual applications have to be explored.